Imperatives of system-based reformation of Ukrainian economics in conditions of crisis. - Чубрей, Олександра; Pidgirna, Valentyna (My University, 2016)
The article deals with actual problems of Ukrainian challenges and obstacles in the country’s way to transformational changes. In this context, the anti-crisis concepts by Paul Krugman, the winner of the 2008 Nobel Memorial Prize in Economic Sciences; those by John Maynard Keynes, the greatest ever economist, as well as the same by leading Ukrainian scientists have been analyzed, and the practicability of their “recipes” to help overcome the present-day Ukrainian crisis was discussed. It has been demonstrated that the regulation measures conducted by the state to help meet the crisis would not lead to increase of unemployment. The components of top-priority crisis-meeting actions have been suggested with simultaneous emphasis on major anti-crisis measures to stabilize the financial-banking sector and develop the domestic market.